Herbivory-induced changes in the small-RNA transcriptome and phytohormone signaling in Nicotiana attenuata - Pandey, Shree P. (National Academy of Sciences, 2008)
Phytohormones mediate the perception of insect-specific signals and the elicitation of defenses during insect attack. Large-scale changes in a plant's transcriptome ensue, but how these changes are regulated remains unknown. Silencing of RNA-directed RNA polymerase 1 (RdR1) makes Nicotiana attenuata highly susceptible to insect herbivores, suggesting that defense elicitation is under the direct control of small-RNAs (smRNAs). Using 454-sequencing, we characterized N. attenuata's smRNA transcriptome before and after insect-specific elicitation in wild-type (WT) and RdR1-silenced (irRdR1) plants. We predicted the targets of N. attenuata smRNAs in the genes related to phytohormone signaling (jasmonic acid, JA-Ile, and ethylene) known to mediate resistance responses, and we measured the elicited dynamics of phytohormone biosynthetic transcripts and phytohormone levels in time-course experiments with field- and glasshouse-grown plants. RdR1 silencing severely altered the induced transcript accumulation of 8 of the 10 genes, reduced JA, and enhanced ethylene levels after elicitation. Adding JA completely restored the insect resistance of irRdR1 plants. irRdR1 plants had photosynthetic rates, growth, and reproductive output indistinguishable from that of WT plants, suggesting unaltered primary metabolism. We conclude that the susceptibility of irRdR1 plants to herbivores is due to altered phytohormone signaling and that smRNAs play a central role in coordinating the large-scale transcriptional changes that occur after herbivore attack. Given the diversity of smRNAs that are elicited after insect attack and the recent demonstration of the ability of ingested smRNAs to silence transcript accumulation in lepidopteran larvae midguts, the smRNA responses of plants may also function as direct defenses.